Evaluation of swelling and permeability properties of films isolated from polymethacrylate containing polysaccharide from Lotus root (Nelumbo nucifera) (Revista Brasileira de Ciências Farmacêuticas, 2004)
Polysaccharides such as extracted from Lotus root (Nelumbo nucifera) combined with polymethacrylates on isolated films for film coating was studied as potential vehicles for colonic drug delivery, susceptible to fermentation by micro flora. For the preparation we used the association of Eudragit®RS 30D and polysaccharides in different concentrations (100:0, 90:10, 80:20, 70:30) in aqueous-based solvents. In the present study, the films were characterized by swelling studies and water vapor transmission studies. These tests demonstrated that different associations do not present significant differences, showing that the physico-chemical properties of EudragitâRS 30D are not altered and this material will be able to be applied for film formation in coating for colonic drug delivery system development.